A fractional delay variable frequency repetitive control for torque ripple reduction in PMSMs - Tang, Mi; Gaeta, Alberto; Formentini, Andrea; Zanchetta, Pericle (Institute of Electrical and Electronics Engineers, 2017)
Based on the internal model principle, repetitive controller (RC) is capable to reduce periodic torque ripple by generating a compensating action that consequently need to be synchronized with the original ripple. However, the synchronization is difficult to achieve using the conventional RC when the sampling frequency is not integer multiple of the speed (known as fractional delay issue), or when the speed varies widely. To solve this problem, this paper presents a fractional delay variable frequency torque ripple reduction method for PMSM drives using the combination of angle-based RC and deadbeat current control (DBCC). Four aspects of innovations are included in the proposed control to improve the synchronization. The experimental results show that the proposed control can effectively reduce torque ripple even during speed and load transient.